Epistemologies of Women Ourselves, Feminisms and Theory from La Selve in the construction of knowledge contributions by the Zapatist Women - Lia Pinheiro Barbosa (Universidade Federal do Norte do Tocantins, 2018)
The article aims to present some elements of our epistemology (epistemologia de nosotras) that articulates the conception of women's struggle erected by the indigenous Zapatista in Chiapas, Mexico. For this, I present the context of political insertion of Zapatista women with the cry of "Já Basta" the Revolutionary Women's Law and the Armed Insurgency of the Zapatista Army of National Liberation (EZLN), highlighting the theoretical-epistemic and political elements that articulate what I call an insurgent, revolutionary, rebellious and autonomous feminism of the Zapatistas.